Nanotechnology-Based Medical Devices for the Treatment of Chronic Skin Lesions: From Research to the Clinic - Marco Ruggeri; Eleonora Bianchi; Silvia Rossi; Barbara Vigani; Maria Cristina Bonferoni; Carla Caramella; Giuseppina Sandri; Franca Ferrari (MDPI AG, 2020)
Chronic wounds, such as pressure ulcers, diabetic ulcers, venous ulcers and arterial insufficiency ulcers, are lesions that fail to proceed through the normal healing process within a period of 12 weeks. The treatment of skin chronic wounds still represents a great challenge. Wound medical devices (MDs) range from conventional and advanced dressings, up to skin grafts, but none of these are generally recognized as a gold standard. Based on recent developments, this paper reviews nanotechnology-based medical devices intended as skin substitutes. In particular, nanofibrous scaffolds are promising platforms for wound healing, especially due to their similarity to the extracellular matrix (ECM) and their capability to promote cell adhesion and proliferation, and to restore skin integrity, when grafted into the wound site. Nanotechnology-based scaffolds are emphasized here. The discussion will be focused on the definition of critical quality attributes (chemical and physical characterization, stability, particle size, surface properties, release of nanoparticles from MDs, sterility and apyrogenicity), the preclinical evaluation (biocompatibility testing, alternative in vitro tests for irritation and sensitization, wound healing test and animal wound models), the clinical evaluation and the CE (European Conformity) marking of nanotechnology-based MDs.